Relasi Pendidikan Orang Tua Dengan Perkembangan Fisik Motorik Anak Usia 5-6 Tahun di RA Kabupaten Pasuruan - Miftahillah Miftahillah (Proceedings of Annual Conference for Muslim Scholars, 2017)
Abstract: The success of parent in the learning process of children at home can not be separated parent good educational background formal, non-formal andinformal. Through playing children actively engage with the environment, and fulfill the tasks of other motor physical development. The problem in this research is the relationsparent education with physical development of the child's motor aged 5-6 years in RA Pasuruan. The purpose of this study was to determine the relation of parenteducation with physical development of the child's motor aged 5-6 years in RA Pasuruan. This study took a sample population of 150 respondents with 5 students STITNU Al Hikmah Mojokerto which following umbrellas research the child's motor physical that each 30 respondents, the data were analyzed using the program processing IBM SPSS Version 21. Conclusion with R2 = 0.259 and F = 10.598 with p = 0.001 (p <0.01). This means that there is a correlation highly significant relationship parent education with physical development of the child's motor, and donations effective parent education = 3.255%. This means that there are 96.745% of the contribution of other variables, such as: factors of heredity, environmental factors natural, social, cultural, nutritional and nutrition and opportunities and exercises.Keywords: Parent Education, Physical Development of the Child's Motor